Tradisi Pesurung Adat dalam Pernikahan Masyarakat Kabupaten Melawi Kalimantan Barat - Yusuf, Yusuf (Institut Agama Islam Negeri Metro, 2023)
One of the characteristics of Islamic Syari'ah is the elimination of difficulties and ease ('Adamul Haraj wat At-Taysir). Many verses of Al-Qur'an and Hadist of the Prophet explicitly explain about this. In fact, this feature can be found in all provisions of the Syari'a, like in a marriage. However, Indonesian society is a society that really keep the richness of culture and customs in a marriage. Even with strict requirements, these customs traditions are considered to be used as a benchmark and consideration in determining law. This article will examine the phenomenon of the Pesurung Adat tradition, in the perspective of Al-'Urf and the principle of eliminating difficulties and facilitating ('Adamul Haraj wat At-Taysir) so that the Pesurung Adat tradition can be seen from the perspective of Islamic law properly. This study analyzes the tradition of Pesurung Adat in the people of Kayu Baong Hamlet, Pekawai Village, Sayan District, Melawi Regency, West Kalimantan. Data obtained by interview method on this tradition. The results showed that this tradition that has been passed down for generations is Al-'Urf As-Shahih (The true tradition), does not contradict the postulates of nash, and as a form of cultural diversity owned by the Indonesian state. The tradition of Pesurung Adat cannot be considered contrary to the principle of 'Adamul Haraj wat At-Taysir because the bridegroom does not object to fulfilling this tradition. If the bridegroom does not have the financial means, the Dewan Adat has agreed that if the bridgroom is unable to fulfill this tradition of Pesurung Adat then he will not be forced to obligate. The findings and studies in this study can be a guide to look at the traditions surrounding marriage, especially those related to giving some finances both before and after the wedding.